MENINGKATKAN KEMAMPUAN BAHASA ANAK USIA DINI MELALUI KEGIATAN PENYEDIAAN BUKU BERGAMBAR : IMPROVING EARLY CHILDREN'S LANGUAGE ABILITY FROM PICTURE BOOK PROVISION ACTIVITIES - MUTIA MUHALISIAH; ASTUTI DARMAYANTI (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2023)
At a young age, children begin to grow and develop rapidly. Educators, parents, caregivers, or other adults around children need to set up a stimulating role by providing a conducive environment for children to reach their full potential. Questions were asked about social, emotional, and independent life, ethical and religious principles, language skills, cognitive, physical/motor, and artistic potential. Language is a tool of communication with other people. The teacher-child approach, which is the subject of this qualitative research, is the method adopted in this study. A method known as